Communication, Artificial Intelligence and the human being’s self-discovery in the digital universe - Frunză, Sandu (Journal for the study of religions and ideologies, 2025)
In the post-truth world, Artificial Intelligence has a significant impact on communication, relationships and human identity, on spirituality, art, culture and politics. In order to understand the profound transformations that take place as a result of the development of communication technologies and the increasingly prominent presence of Artificial Intelligence, I turned to the analyses of the philosopher Aurel Codoban. From this perspective, digital technologies determine radical changes in the way in which the human being relates to himself and to otherness, including the radical otherness represented by AI. Relating to otherness helps man to understand his uniqueness, especially in terms of personal experience and his creative function. While Artificial Intelligence can have extensive knowledge and can be a very good content generator, creativity remains, for now, the prerogative of the human being understood as a "holographic shard" that reflects the singularity of life. In the differentiations between Artificial Intelligence and the human being, I insisted on spiritual factors, on symbolic understanding and on the awareness of uniqueness built in relation to otherness. The transformations brought by the digital world force us to rethink communication practices from the perspective of the reconstruction of the self and the recovery of the spiritual dimension of the human being, with all the symbolism implied by the image of placing man at the center of existence as such. Technological alienation must be overcome by cultivating creativity, interiority and meaning in a digital universe saturated with cultural content.